2014
DOI: 10.1002/uog.13249
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor biometry in Chinese primiparous women 1 year after delivery: a prospective observational study

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 28 publications
(50 reference statements)
3
47
0
1
Order By: Relevance
“…Previous studies with shorter follow up have found recovery of bladder neck mobility from assessment soon after delivery up to one year later, but they found still higher values when compared to pregnancy levels . We found increased values for all ultrasound variables over time, and in particular, we found an increase in ultrasound variables from 1 year to 4 years postpartum.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous studies with shorter follow up have found recovery of bladder neck mobility from assessment soon after delivery up to one year later, but they found still higher values when compared to pregnancy levels . We found increased values for all ultrasound variables over time, and in particular, we found an increase in ultrasound variables from 1 year to 4 years postpartum.…”
Section: Discussionsupporting
confidence: 48%
“…Increased bladder neck and urethral mobility have been identified after VD compared to CS, in particular after operative vaginal deliveries . However, some authors have postulated that differences between modes of delivery attenuate with time . We observed a tendency to increased bladder neck and urethral mobility after VD compared to CD.…”
Section: Discussionmentioning
confidence: 40%
“…van Veelen et al [13] studied 280 nulliparas at 12 and 36 weeks prospectively and concluded that the dimensions, contractility, and distensibility of the LH significantly increase in the 3 rd [11] demonstrated that all hiatal dimensions and the mobility of the bladder neck increase significantly from 21 to 37 weeks of gestation in a prospective study of 274 nulliparas. The effect of pregnancy in the dimensions of the LH is clearly demonstrated in the study of Chan et al [12], in which all the Chinese nulliparas who participated in the study showed a significant increase in the LH dimensions as the pregnancy progressed.…”
Section: Changes In the Lh Dimensions During Pregnancymentioning
confidence: 91%
“…Pregnancy itself appears to be a risk factor for developing PFDs [11,20]. Moreover, Chan et al supported in their study that pregnancy beyond the 35 th week has an effect on the pelvic floor of Chinese women independently of the delivery mode [12]. Further evidence is warranted to explain the exact mechanism of the alterations in the pelvic floor during gestation.…”
Section: Changes In the Lh Dimensions During Pregnancymentioning
confidence: 94%
See 1 more Smart Citation